MAJOCCHI’S GRANULOMA OF THE VULVA – A CASE REPORT - Bjekic, Milan; Pecarski, Danijela (HEALTH CARE, 2020)
Introduction/Aim: Majocchi’s granuloma is an infrequent deep-seated fungal infection where pathogen invades hair follicles, entering the dermal and subcutaneous tissue, thus forming granulomatous dermal and/or hypodermal changes. There are two clinical types: the first one is common in healthy individuals characterized by superficial perifollicular papular infection, and the second is followed by the deep subcutaneous nodules usually reported among immunocompromised hosts. This infection is usually caused by Trichophyton rubrum. The aim of this paper is to show the rare localization of this disease in the area of the vulva. Case report: We present a 20-year-old immunocompetent woman with multiple papules, nodules, and pustules on the hairy part of the vulva. Potassium hydroxide preparations of skin scrapings were negative and culture performed on Sabouraud glucose agar revealed Trichophyton rubrum. The patient was treated with the oral systemic antifungal therapy for four weeks and all lesions resolved. Conclusion: Majocchi’s granuloma should not be overlooked in patients with papular and nodular lesions in the vulvar region.